Spiritual leadership : moving people on to God's agenda - Blackaby, Henry T., 1935-; Blackaby, Richard, 1961- (Nashville, Tenn. : Broadman & Holman Publishers, 2001)
Presents insights and guidance on developing and maintaining one's spiritual leadership skills
The leader's challenge -- The leader's role : what leaders do -- The leader's preparation : how God develops leaders -- The leader's vision : where do leaders get it and how do they communicate it? -- The leader's character : a life that moves others to follow -- The leader's goal : moving people on to God's agenda -- The leader's influence : how leaders lead -- The leader's decision making -- The leader's schedule : doing what's important -- The leader's pitfalls : what disqualifies leaders? -- The leader's rewards
Includes bibliographical references (pages 289-299) and index
Keywords: Leadership -- Religious aspects -- Christianity